(untitled) - Pillay, T. V. R. (Oxford, Eng, 1990)
Covering all aspects of subsistence and commercial aquaculture as practiced across the globe, this fully revised new edition from two leading world authorities in the field is set in two parts: principles and practices, and covers in detail recent developments in: History and planning, nutrition, reproduction and genetic selection, production statistics and economics, integrated aquaculture and sustainability and environmental effects
Chuyên đề tổng hợp kiến thức cơ sở NLTS
Keywords: Aquaculture